2014
DOI: 10.1183/09031936.00184314
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent hypoxia alters gut microbiota diversity in a mouse model of sleep apnoea

Abstract: We assessed whether intermittent hypoxia, which emulates one of the hallmarks of obstructive sleep apnoea (OSA), leads to altered faecal microbiome in a murine model.In vivo partial pressure of oxygen was measured in colonic faeces during intermittent hypoxia in four anesthetised mice. 10 mice were subjected to a pattern of chronic intermittent hypoxia (20 s at 5% O 2 and 40 s at room air for 6 h·day −1 ) for 6 weeks and 10 mice served as normoxic controls. Faecal samples were obtained and microbiome compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
213
3
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 229 publications
(239 citation statements)
references
References 31 publications
11
213
3
4
Order By: Relevance
“…Similarly, gut microbiota metabolites have been reported to be altered in sleep-deprived humans 35. Along the same lines, intermittent hypoxia has been found to alter gut microbiota diversity in OSA mice models 36. Moreover, we also found a family of phenols, including cresol, which is a unique bacterial metabolite from protein fermentation 37.…”
Section: Discussionsupporting
confidence: 63%
“…Similarly, gut microbiota metabolites have been reported to be altered in sleep-deprived humans 35. Along the same lines, intermittent hypoxia has been found to alter gut microbiota diversity in OSA mice models 36. Moreover, we also found a family of phenols, including cresol, which is a unique bacterial metabolite from protein fermentation 37.…”
Section: Discussionsupporting
confidence: 63%
“…For example, recent work suggests an effect of CPAP on circulating levels of glucagon-like protein-1, a satiety hormone [104]. Interestingly, an animal model of OSA found that induced intermittent hypoxia in mice caused alterations in microbiota composition and diversity [105], suggesting the testing of CPAP on this outcome. Based on findings that sleep restriction can affect brain regions involved in motivation and reward in the context of food stimuli [106], new work should also extend beyond the hormonal/homeostatic control of energy intake, to determine how CPAP affects the hedonic and cognitive control of food intake in OSA patients, using functional brain imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Under such circumstances, altered gut microbiota could lead to obesity and metabolic dysfunction [120-122]. Similarly, gut microbiota could be perturbed by the presence of OSA and trigger inflammation [123]. LPS-binding protein (LBP) serves as a surrogate marker of underlying low-grade endotoxemia by LPS from the gut.…”
Section: Obesity and Obstructive Sleep Apnea Syndrome: Bad Bad Andmentioning
confidence: 99%